Multiple hydatid cyst disease revealed by an expansive intracranial process: A case report. Issue 3 (15th March 2023) - Nechi, Salwa; Gharbi, Ghada; Douggaz, Amel; Belfekih, Houda; Chaabane, Abir; Mfarrej, Mohamed Karim; Chelbi, Emna
Abstract: Hydatid disease is a real public health problem in developing countries. Cerebral localization is rare; it does not exceed 2%. It is more frequent in children and adolescents. It is often primary in children. In adults, it is less frequent and generally associated with other localizations. We report the case of a 60‐year‐old Tunisian patient with pulmonary, hepatic and cerebral hydatid cyst, revealed by neurological symptoms with an expansive intracranial process on brain imaging. Abstract : The brain is a rare location of hydatid disease, especially in adults. It is rarely isolated. Thus, other localizations must be screened systematically. Brain hydatid cyst can be life threatening. An early diagnosis and an adequate treatment of this rare location of the disease are thus mandatory.